Methodological implications of a systems approach to organizational climate - Sonja Verwey (Communicare)
In this article the serious theoretical and methodological issues facing climate research are discussed. It is indicated that the most important theoretical and methodological issue facing climate researchers is a lack of conceptual In tegration of the climate construct. It is shown that this has resulted in an In ablilty of climate researchers to satisfactorily resolve a number of methodological Issues. It is further shown that the Inability of climate researchers to resolve these methodological Issues, has led to a decline of research interest in the climate construct, whereby the viabill ty of organizational climate as a research field and management tool Is threatened. In this article the author proffers a social systems approach to the conceptualization of organizational climate. The methodological implications of such an approach are discussed and it Is shown that this reconceptualization of the climate construct can alleviate many of the methodological Issues still facing climate research.